Eros em pauta: a sexualidade nas páginas do Jornal Notícias Populares (1982-1984) - Piacsek, Eduardo Guilherme (2014)
This work aims to analyze how the São Paulo newspaper Notícias Populares (NP) dealt with the topic of sexuality between 1982 and 1984. This issue gained special prominence in Brazilian society during this period, which was the end of the military dictatorship that started in 1964. To achieve our goal, we will study the column Tudo Sobre Sexo (All About Sex) published in the newspaper since 1982 and dedicated to providing its readers with scientific information; we will analyze the reports of Histórias da Boca, a series of narratives written by NP crime reporters and set on downtown São Paulo, an area known as "Boca do Lixo", a workplace of prostitutes, transvestites and swindlers; and finally, we will draw attention to the progressive increase in the number of stories that the newspaper devoted to the topic of sexuality, with special emphasis on its coverage of the rise of the AIDS epidemic, a lethal sexually transmitted disease and the appearance of Roberta Close in the media, a transsexual who reached the status of sex symbol in Brazil. In this work, the newspaper Notícias Populares, symbol of Brazilian tabloid press, will be treated not as a counterpoint to what is regarded as serious journalism, but as a vehicle of mass communication able to achieve complex representations and meanings